Technical wood veneer carbon-based light energy-saving material and cabinet door plate product thereof

By integrating bamboo charcoal, activated carbon and thermoplastic polymers and combining technological wood veneer, a tech wood veneer carbon-based lightweight energy-saving material has been developed, which solves the challenges of traditional cabinet door panel materials in resource conservation, environmental protection, functional diversity and aesthetics, and achieves the effects of lightweight, high-strength, thermal insulation, low formaldehyde emission and diverse decoration.

CN119635775APending Publication Date: 2025-03-18DEHUA TB NEW DECORATION MATERIAL CO LTD

Patent Information

Application Number
CN202411870059.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Traditional cabinet door panel materials have challenges in resource conservation, environmental protection, functional diversity and aesthetics, including scarce solid wood resources, easy deformation, high formaldehyde emission, large weight and difficult to install, and insufficient thermal insulation performance, resulting in increased energy consumption.

Method used

By integrating environmentally friendly materials such as bamboo charcoal and activated carbon with thermoplastic polymers, and combining technological wood veneer, a tech wood veneer carbon-based lightweight and energy-saving material has been developed. This material uses bamboo processing residue to make bamboo charcoal powder and activated carbon powder. Combined with bamboo powder and thermoplastic polymers, it forms lightweight, high-strength, thermal insulation, and low formaldehyde emission properties, and ensures the stable adhesion of the wood veneer and the core material through water-based environmentally friendly heteroadhesive adhesives.

Benefits of technology

It realizes efficient recycling of resources, reduces dependence on original wood, reduces costs and enhances environmental performance. This material has excellent properties such as lightweight and high strength, thermal insulation, and low formaldehyde emission. It has rich decorative effects, meeting the needs of modern consumers for high-quality and personalized home decoration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides an engineered wood veneer carbon-based light energy-saving material and a cabinet door plate product thereof. The engineered wood veneer carbon-based light energy-saving material comprises a carbon-based core material and an engineered wood veneer, the carbon-based core material comprises 25-60 parts of bamboo charcoal powder, 5-15 parts of bamboo activated carbon powder, 10-20 parts of bamboo powder, 40-70 parts of thermoplastic polymer master batch and 1-10 parts of processing auxiliary materials; the technical wood veneer comprises a technical wood veneer and a water-based environment-friendly heterogeneous adhesive. The material is prepared by preparation of a carbon-based core material and processing and compounding of a technical wood veneer, wherein the preparation of the carbon-based core material comprises the steps of batching and weighing, high-speed stirring, melting and granulating, re-mixing and molding and post-processing; technical wood veneer processing and compounding cover veneer preparation, adhesive blending, uniform gluing, assembly pre-pressing and three-section type cold pressing curing. According to the technical wood veneer carbon-based light energy-saving material and the cabinet door plate product thereof, through material formula design and preparation process planning, light weight, high strength, heat insulation, low formaldehyde release and diversified decoration are integrated, and the low-cost environment-friendly target of resource recycling is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of building decoration materials, and in particular to a carbon-based lightweight energy-saving material with a technological wood veneer and a cabinet door panel product thereof, which integrates the characteristics of bamboo charcoal with the advantages of technological wood veneer to provide a new material with both functionality and decoration and a preparation scheme thereof. Background Art

[0002] In the field of architectural decoration and furniture manufacturing, the requirements for material performance are becoming more and more stringent, especially in terms of resource conservation, environmental protection, and meeting diverse aesthetic and functional needs. Traditional cabinet door panel materials face many challenges. Solid wood, with its natural and beautiful texture and feel, once occupied an important position in the market. However, its long growth cycle has led to scarce resources, high costs, and difficult large-scale sustainable applications. At the same time, under complex and changing environmental conditions, solid wood is prone to deformation and cracking. Subsequent maintenance work is not only time-consuming and labor-intensive, but also requires a lot of money. In southern regions with high humidity, it is common for solid wood cabinet door panels to deform due to moisture, which greatly affects the service life and aesthetics of furniture. Although wood-based panels such as density boards and particle boards are widely used due to their low cost and simple processing, their high formaldehyde release cannot be ignored. Formaldehyde, as one of the main sources of indoor air pollution, seriously threatens human health. Long-term exposure to high-concentration formaldehyde can cause respiratory diseases, allergic reactions, and even cancer. In addition, these traditional panels are heavy in weight. In scenarios where lightweight requirements are high, such as movable cabinets and furniture in high-rise buildings, the difficulty and cost of transportation and installation are significantly increased, and additional pressure is placed on the building structure, bringing potential safety hazards. Taking the transportation of furniture in high-rise buildings as an example, the heavier panels not only increase the labor intensity and risk of the movers, but also cause damage to the floor structure due to overweight.

[0003] At the same time, the intensification of the global energy crisis and the continuous improvement of people's environmental awareness have prompted the construction and furniture industries to have an increasingly urgent demand for energy-saving and environmentally friendly materials. The lack of thermal insulation performance of traditional materials has led to frequent heat exchange between indoors and outdoors and high energy consumption, which runs counter to the current theme of energy conservation and emission reduction. In this context, technological wood uses fast-growing wood or small-diameter wood as raw materials, and with the help of special processing technology and technical means, accurately simulates the texture and color of natural wood, effectively alleviates the dilemma of shortage of natural wood resources, and realizes the sustainable use of wood resources. By cleverly changing the production process and adding functional ingredients, its performance can be flexibly adjusted. After adding waterproofing agents and fire retardants, the waterproof and fire retardant properties are significantly enhanced; optimizing the fiber structure and composite process can greatly improve the mechanical properties and stability. Moreover, technological wood can realistically imitate the texture and color of various rare woods, and can create unique visual effects that natural wood does not have, opening up a broad creative space for furniture and decoration design, and fully satisfying consumers' pursuit of personalization and beauty.

[0004] Carbon-based materials such as activated carbon and bamboo charcoal have unique pore structures and huge specific surface areas, and have excellent adsorption properties. They can effectively absorb harmful gases, odors, and moisture in the air, and play a key role in purifying the air and regulating humidity. They effectively reduce the harm of harmful substances such as formaldehyde and benzene to the human body, and effectively improve the quality of the indoor environment. Some new carbon-based composite materials, such as carbon fiber reinforced composite materials, have the characteristics of light weight, high strength, and high modulus. While reducing the weight of cabinet door panels, they ensure or even improve the mechanical properties of the materials, which brings great convenience to installation and use. Not only that, its good electrical and thermal conductivity creates possibilities for innovative applications in the fields of smart furniture and energy conservation. Combined with intelligent control systems, it can realize cutting-edge functions such as temperature regulation and intelligent sensing of cabinet door panels. The development of new materials and their cabinet door panel products is in line with industry development trends and market demand, and is a need of the times. Summary of the invention

[0005] The purpose of the present invention is to provide a carbon-based lightweight energy-saving material of a technological wood veneer and its cabinet door panel products. By integrating environmentally friendly materials such as bamboo charcoal and activated carbon with thermoplastic polymers, full use is made of bamboo processing residues, and efficient resource recycling is achieved, reducing dependence on original wood, cutting costs and enhancing environmental protection performance; through precise design of material formula and rigorous planning of preparation process, the material is given excellent properties such as light weight and high strength, heat insulation, and low formaldehyde release. Its technological wood veneer can present rich decorative effects, which is in line with the pursuit of high-quality and personalized home decoration by modern consumers, and opens up a new path for the innovative development of cabinet door panel materials, leading the industry to a more environmentally friendly, higher-quality and more diversified development stage.

[0006] The technological wood veneer carbon-based lightweight energy-saving material of the present invention, its carbon-based core material contains bamboo charcoal powder, bamboo activated carbon powder, bamboo powder, thermoplastic polymer masterbatch and processing auxiliary materials in a specific proportion, bamboo charcoal powder provides adsorption and stability, activated carbon powder strengthens adsorption, bamboo powder optimizes physical properties, polymer masterbatch ensures processability, and auxiliary materials improve the process; the technological wood veneer carbon-based lightweight energy-saving material, its technological wood veneer is composed of technological wood veneer and water-based environmentally friendly heterogeneous adhesive, the veneer increases beauty and creativity, and the adhesive ensures composite stability and environmental protection; the overall realization of resource recycling, cost reduction, and improved environmental protection performance, integrating light weight and high strength, heat insulation, low formaldehyde release and diverse decoration.

[0007] The invention provides a carbon-based lightweight energy-saving material for a technological wood veneer, the material composition of which includes a carbon-based core material and a technological wood veneer; the carbon-based core material includes 25-60 parts of bamboo charcoal powder, 5-15 parts of bamboo activated carbon powder, 10-20 parts of bamboo powder, 40-70 parts of thermoplastic polymer masterbatch, and 1-10 parts of processing auxiliary materials; the technological wood veneer includes technological wood veneer and a water-based environmentally friendly heterogeneous adhesive.

[0008] The proportion of ingredients in the formula of the carbon-based lightweight energy-saving material of the technological wood veneer balances the performance requirements of all parties. The content of bamboo charcoal powder and bamboo activated carbon powder is appropriate, which not only builds a strong adsorption and purification system, efficiently removes pollutants such as formaldehyde and benzene, optimizes indoor air quality, but also avoids excessive brittleness or processing difficulties of the material due to excessive amount; the proportion of bamboo powder enhances the mechanical properties of the material, gives it excellent strength and toughness, effectively resists deformation and cracking, and does not sacrifice adsorption characteristics and processability; the proportion of thermoplastic polymer masterbatch is appropriate, which ensures the smoothness and molding accuracy of the material's thermal processing, and it is easy to shape complex-shaped products. The processing auxiliary materials are trace and efficient, which improves the processing quality. The various ingredients complement each other and achieve the dual advantages of function and processing characteristics. Among them, the core ingredients such as bamboo charcoal powder made from bamboo processing residues greatly expand the resource recycling path, reduce the consumption of original wood, reduce costs, improve benefits, and effectively implement the concept of environmental protection; the proportion of water-based environmentally friendly heterogeneous adhesive ingredients in the technological wood veneer is finely adjusted, which significantly reduces the emission of volatile organic compounds, creates a healthy indoor environment, and meets green standards. The technological wood veneer carbon-based lightweight energy-saving material of the present invention optimizes the proportion of ingredients throughout the entire process from the source of raw materials to the entire processing, taking into account both environmental responsibility and economic considerations.

[0009] Specifically, in the material composition of the carbon-based lightweight energy-saving material of the technological wood veneer of the present invention, the multiple components of the carbon-based core material synergize to enhance the efficiency, and the combination of technological wood veneer materials enhances the integration of decoration and function. Among them, the bamboo charcoal powder is derived from the pyrolysis of the residues of bamboo processing, which lays the foundation for the basic characteristics. Its specific carbonization temperature is 500-800℃, density is 0.6-0.8g / cm³, ash content is 0.5-3%, specific surface area is 250-350m² / g and particle size range is 60-325 mesh, which gives the material good adsorption and chemical stability, can absorb odor, adjust humidity, stabilize the internal structure of the material, prevent decay and decomposition, and the source is environmentally friendly, which meets the demand for resource recycling; bamboo activated carbon powder, as a bamboo charcoal activation product, enhances the adsorption function, and its specific surface area is 50-150m² / g, which is the same as the average The average pore size is 2-4nm, which complements the bamboo charcoal powder, improves the adsorption of small molecular harmful substances such as formaldehyde and benzene, purifies the air, optimizes the indoor environment, ensures living health, and enhances the environmental protection advantages of the material; 50-60 mesh bamboo powder is filled in the material matrix and interwoven with other ingredients to form a stable network structure, optimize physical properties, and improve strength and toughness without significant weight gain. It can effectively resist external impact, stretching and bending, prevent deformation and fracture, extend service life, and broaden application scenarios, such as maintaining shape stability in cabinet door panels that are frequently opened and closed; thermoplastic polymer masterbatch ensures molding processability and high temperature The softening and cooling solidification characteristics enable the material to be processed into complex shapes through melt blending, extrusion molding and other processes, ensuring dimensional accuracy and appearance quality, meeting diverse design and manufacturing needs, improving production efficiency, reducing costs, and achieving large-scale mass production; lubricants and release agents such as stearic acid are used as processing auxiliary materials to improve material fluidity and demoulding properties, reduce processing energy consumption and equipment loss, improve product surface finish, reduce defects, improve overall processing quality and economic benefits, and ensure production continuity and stability; technological veneer simulates the texture and color of natural wood, and technological veneer reproduces the visual effects of rare wood and creates unique textures , enhance the artistic value and decorativeness of the product, provide consumers with a variety of style choices, and meet the pursuit of personalized home decoration; water-based environmentally friendly heterogeneous adhesives are adhesives formulated with water-based polyurethane dispersions, acrylic emulsions, etc. that are suitable for veneer and core materials. After curing, strong bonding chemical bonds are formed to tightly bond the veneer and core material to prevent stratification and peeling, improve structural stability, and ensure composite reliability and environmental protection. The water-based system reduces volatile organic compound emissions, and multiple curing agents synergistically optimize the curing speed and cross-linking density, enhance water resistance, heat resistance, and aging resistance, adapt to complex use environments, and expand the scope of application.

[0010] Preferably, the bamboo charcoal powder in the carbon-based core material has a carbonization temperature of 500-800°C, a density of 0.6-0.8g / cm³, an ash content of 0.5-3%, a specific surface area of ​​250-350m² / g, and a particle size of 60-325 mesh, and is derived from the pyrolysis of bamboo processing residues; the bamboo activated carbon powder is a bamboo charcoal activation product, with a specific surface area of ​​50-150m² / g and an average pore size of 2-4nm; the particle size of the bamboo powder is 50-60 mesh; the thermoplastic polymer masterbatch is a thermoplastic resin; and the processing auxiliary materials include lubricants and release agents such as stearic acid.

[0011] Among them, the carbonization temperature range of bamboo charcoal powder is precisely controlled at 500-800℃, which promotes the orderly pyrolysis and transformation of the organic components of bamboo, shapes the ideal microscopic pore structure and crystal structure, and gives the material strong adsorption and chemical stability characteristics; the appropriate density of 0.6-0.8g / cm³ balances the weight and mechanical properties of the material, avoids excessive weight while ensuring strength, and meets the needs of lightweight, such as reducing the burden in the application of movable cabinet door panels; the ash content range of 0.5-3%, the high specific surface area of ​​250-350m² / g and the reasonable particle size of 60-325 meshes work together to improve Adsorption and purification efficiency, optimization of internal structure and dispersion, strengthening of material stability and functionality, making full use of bamboo processing residues, and practicing the concept of environmental protection and efficient use of resources; the activated carbon powder obtained by bamboo charcoal activation, 50-150m² / g specific surface area and 2-4nm average pore size are precisely adapted to form a high-efficiency adsorption channel and active site network, targeted capture of small molecule harmful substances, complementary with bamboo charcoal powder, greatly improving the material's ability to purify air and regulate humidity, and improving indoor environmental quality; 50-60 mesh bamboo powder particle size is strictly screened filling material The system has a moderate particle size to ensure good dispersibility and fluidity, and is closely interwoven with other ingredients to form a stable three-dimensional network, which enhances the overall mechanical properties of the material, effectively resists deformation and cracking caused by external forces, improves impact resistance and fatigue resistance, prolongs service life, expands the breadth and depth of application, and stabilizes the structure of cabinet door panels; thermoplastic resin is the core of the masterbatch, and its high-temperature melting and cooling solidification characteristics enable the material to be accurately formed in processes such as twin-screw extrusion, meeting the requirements of complex shapes, dimensional accuracy and appearance quality, adapting to diversified design and manufacturing, improving production efficiency, reducing costs, and promoting large-scale production, providing guarantees for the industrial application of materials and improving product consistency and reliability; processing auxiliary materials such as stearic acid, lubricants, and release agents are key additives in the processing flow. Lubricants reduce internal friction of materials, enhance fluidity, ensure uniform heating and mixing, and prevent agglomeration and overheating degradation; release agents weaken the adhesion between materials and molds, reduce demolding force, improve demolding efficiency and product surface quality, and reduce defective defects. The two work together to optimize processing parameters, reduce equipment energy consumption and wear, improve production continuity and stability, improve comprehensive economic benefits, and enable high-quality material manufacturing.

[0012] The water-based environmentally friendly heterogeneous adhesive in the technological wood veneer of the carbon-based lightweight energy-saving material of the technological wood veneer of the present invention has achieved all-round improvement in terms of bonding effect, environmental protection characteristics and processing performance by virtue of the design of its components and proportions. At the bonding level, a variety of key ingredients, including water-based polyurethane dispersion, acrylic emulsion, polyisocyanate curing agent and epoxy curing agent, are cross-linked in a specific proportion to weave a strong chemical bond network between the technological wood veneer and the carbon-based core material. This stable bonding can resist the mechanical stress caused by the frequent opening and closing of the cabinet door in daily life, and the deformation stress caused by changes in temperature and humidity. It can always maintain the stability of the composite structure of the material during long-term use, prevent delamination and peeling, effectively extend the service life of the cabinet door panel, reduce maintenance costs, and enhance the user's convenience and comfort experience. In terms of environmental protection characteristics, the adhesive takes the water-based system as its core feature, uses water as a solvent carrier to significantly reduce or even eliminate dependence on traditional organic solvents, curbs volatile organic compound emissions from the source, optimizes the solid content and compounding ratio of the two-component water-based isocyanate, and finely controls the progress and degree of the curing reaction. While ensuring a strong bond, harmful volatiles are reduced to a minimum, effectively avoiding the risk of air pollution. At the same time, an appropriate amount of defoaming agent is introduced to accurately capture and eliminate bubbles generated during the preparation and coating of the adhesive, to prevent them from remaining on the bonding interface and forming defects that weaken the bonding, to ensure that the adhesive layer is dense and uniform, and to improve the overall bonding quality and appearance smoothness; an appropriate amount of thickener is used to adjust the viscosity curve, and it is flexibly adapted to the coating process such as roller coating and spraying to ensure uniform glue coating, smoothness and accuracy, and achieve uniform and controllable thickness of the adhesive layer, thereby improving processing efficiency and quality stability; a multi-curing agent synergistic enhancement mechanism gives the adhesive excellent water resistance, heat resistance, and aging resistance, allowing it to maintain stable bonding and protective functions in complex environments such as humid kitchens and bathrooms, high-temperature outdoor environments, etc., broaden the application boundaries of materials in outdoor and high-humidity scenes, and comprehensively improve the environmental adaptability and functionality of the product, expanding the scope of market application.

[0013] Preferably, the water-based environmentally friendly heterogeneous adhesive in the technological wood veneer is compatible with the technological wood veneer and the carbon-based core material, and the water-based environmentally friendly heterogeneous adhesive includes: 40-60 parts of water-based polyurethane dispersion, 20-40 parts of acrylic emulsion, 10-20 parts of polyisocyanate curing agent, 5-10 parts of epoxy curing agent, 0.1-0.5 parts of defoaming agent, and 0.5-2 parts of thickener; the solid content of the two components of water-based isocyanate including the water-based polyurethane dispersion and the polyisocyanate curing agent in the water-based environmentally friendly heterogeneous adhesive is 40-60%, and the compounding ratio with the curing agent is 100:6-15.

[0014] The adhesive is carefully formulated with a ratio of ingredients to perfectly match the technical veneer and carbon-based core material. It is based on 40-60 parts of waterborne polyurethane dispersion and 20-40 parts of acrylic emulsion, which work together to provide excellent adhesion and flexibility. During curing, it cross-links with 10-20 parts of polyisocyanate curing agent and 5-10 parts of epoxy curing agent to build a tough chemical bond network, tightly bond the veneer and core material, eliminate the risk of delamination, and stabilize the overall structure. Under the stress of frequent opening and closing of the cabinet door panel, this strong adhesion ensures the stability of the material interface, maintains shape accuracy and mechanical integrity, extends service life, and improves product durability and reliability. The water-based system is dominant, and water is used as the dispersion medium to greatly reduce the use of organic solvents, reduce volatile organic compound emissions from the source, and the 40-60% water-based isocyanate two-component solid content and the precise compounding ratio of 100:6-15 optimize the curing process while ensuring the quality of the adhesive. It can significantly improve the air quality and protect the health of residents in indoor furniture applications, which is in line with environmental protection regulations and the market's strong demand for green products; 0.1-0.5 parts of defoamer can effectively eliminate bubbles in the mixing and coating process, avoid pore defects, improve the density of the bonding interface and the uniformity of the glue layer, and enhance the overall physical properties of the material; 0.5-2 parts of thickener can accurately control the viscosity, adapt to the process requirements of roller coating, spraying, etc., ensure uniform coating and precise thickness control, and optimize processability and construction efficiency; the multi-curing agent synergistic curing mechanism optimizes the water resistance, heat resistance and aging resistance of the adhesive, making it durable and stable in complex environments such as humidity, high temperature and light, such as kitchen, bathroom cabinet door panels or outdoor furniture applications. Maintain excellent bonding and decorative functions, greatly broaden the scope of application of the material, unlock multiple application scenarios, and improve product versatility and environmental adaptability.

[0015] Preferably, the present invention provides a carbon-based lightweight energy-saving material for a technological wood veneer, and the preparation method thereof specifically comprises the following steps: S1 carbon-based core material preparation: S11 Ingredient weighing: accurately weigh 25-60 parts of bamboo charcoal powder, 5-15 parts of bamboo activated carbon powder, 10-20 parts of bamboo powder, 40-70 parts of thermoplastic polymer masterbatch, and 1-10 parts of processing auxiliary materials, and pre-bake and heat each material component for 1-2 hours; S12 high-speed stirring: put the weighed bamboo charcoal powder, bamboo powder, thermoplastic polymer masterbatch and processing auxiliary materials into a high-speed mixer, and stir continuously at 1200-1500r / min for 5-10 minutes to ensure that the materials are evenly mixed; S13 melt granulation: the uniformly stirred mixture is transferred to a twin-screw extruder, melt-blended therein, and granulated after extrusion, with the particle size controlled at 10-20 meshes; S14: Mixing and molding again: first, the obtained particles are stirred in a high-speed mixer for 30-60 seconds, then the bamboo activated carbon powder after high-temperature carbonization is added, and stirring is continued for 1-2 minutes, and then the mixture is put into a twin-screw extruder for melt blending and extrusion, and a plate-shaped extrusion mold is used, and water cooling is performed after extrusion; S15 post-processing: Cut the cooled and shaped plates into the standard size required for production, inspect the plates with multiple indicators, and obtain qualified carbon-based core materials for standby use; S2 technology wood veneer processing and compounding; S21 veneer preparation: Dry the technical wood veneer to a moisture content of 8%-12%, pre-bake at 60-80℃ for 2-4 hours, and cut into the same size as the carbon-based core material; S22 adhesive preparation: according to the proportion, take 40-60 parts of waterborne polyurethane dispersion, 20-40 parts of acrylic emulsion, 10-20 parts of polyisocyanate curing agent, 5-10 parts of epoxy curing agent, 0.1-0.5 parts of defoaming agent, and 0.5-2 parts of thickener to prepare waterborne environmentally friendly heterogeneous adhesive, stir at room temperature at 800-1000r / min for 20-30 minutes, and vacuum degassing at -0.08 to -0.1MPa for 10-15 minutes; S23 Uniform Gluing: Use roller coating or spraying to evenly apply glue to the surface, and the amount of glue applied is controlled at 70-130g / ㎡; S24 pre-pressing of the assembly: After the adhesive surface and the carbon-based core material surface are accurately fitted, they are quickly sent into the pre-pressing machine and lightly pressed at a pressure of 0.4-0.6MPa for 5-10 minutes; S25 cold pressing and curing: The carbon-based core material and the high-tech wood veneer composite with the glue-coated surface precisely fitted are then transferred to the cold press, where they are compacted using a three-stage cold press with a pressure of 1.0-2.0MPa and a time of 1.0-3.5h according to the set parameters. The ambient temperature is controlled at 15-25℃ and the humidity at 40-60% throughout the process to obtain the composite carbon-based lightweight energy-saving material with high-tech wood veneer.

[0016] In the preparation method of the material of the present invention, the melt granulation step realizes sufficient melt blending of materials, precise temperature control, particle size specification and re-melting of unqualified particles by setting relevant parameters of the twin-screw extruder, thereby ensuring material uniformity, improving material performance, ensuring stable quality, and improving production efficiency and product qualification rate.

[0017] Preferably, the preparation method of the technological wood veneer carbon-based lightweight energy-saving material step S13 melt granulation specific operation includes: inputting the stirred mixture into a twin-screw extruder, setting the screw speed to 200-300r / min for full melt blending, controlling the barrel temperature at 160-190°C, setting the temperature zone according to the material characteristics, the feed section 160-170°C, the compression section 175-185°C, the metering section 180-190°C, the die head pressure is set to 12-18MPa,, the obtained particle size is controlled at 10-20 mesh, and the particles are screened and graded by a vibrating screen, and the non-compliant particles are returned for reprocessing. By setting the screw speed of 200-300r / min, the mixture can be fully melt blended in the twin-screw extruder, ensuring uniform mixing between the components, avoiding local component differences, and laying the foundation for the consistency of subsequent material properties. The barrel temperature is controlled at 160-190℃ and is set in different temperature zones according to the material characteristics. Different temperature zones can keep the material in the most suitable temperature environment at each stage such as feeding, compression and metering, ensuring the good melting state of the material, promoting chemical reactions and physical fusion between the components, and improving the comprehensive performance of the material. The die pressure is set to 12-18MPa, so that the particle size of the extruded particles is controlled at 10-20 mesh. After screening and grading by a vibrating screen, particles with uniform particle size can be obtained, which helps to improve the density uniformity, mechanical properties and appearance quality of the material, making its performance more stable and reliable during subsequent processing and use. The operation of returning non-compliant particles for reprocessing reduces the waste of raw materials and ensures the quality of the final product. Through the fine control of the entire melt granulation process, the controllability and stability of the production process are improved, thereby improving the overall production efficiency and product qualification rate.

[0018] The specific parameter settings of the high-speed mixer, twin-screw extruder and water-cooled molding system in the re-mixing and molding steps in the preparation method of the material of the present invention improve the material's adsorption and mechanical properties, processability, structural stability, dimensional accuracy and appearance quality through efficient and uniform mixing, optimized extrusion molding and precise water-cooling shaping, thereby ensuring high performance and high quality of the product and meeting the needs of multiple applications.

[0019] Preferably, in the preparation method of the technological wood veneer carbon-based lightweight energy-saving material in step S14 of the re-mixing and molding, the stirring blade of the high-speed mixer adopts a double-layer three-blade type, the ratio of the upper blade radius to the lower blade is 1-2:1, and the rotation speed is 1300-1500r / min; the twin-screw extruder is set to a temperature of 170-190°C, a pressure of 6-10MPa, and a time of 5-10 minutes; the water-cooled molding system adopts multi-nozzle spray water cooling, a water pressure of 0.3-0.5MPa, a water temperature of 10-20°C, and a cooling rate of 50-80°C / s circulating water quenching. The high-speed mixer uses a specific double-layer three-blade impeller with an upper and lower layer radius ratio of 1-2:1 and a speed of 1300-1500r / min, so that the first-mixed particles and the subsequently added bamboo activated carbon powder are quickly and fully mixed, ensuring that the activated carbon powder is evenly dispersed in the material, thereby improving the overall adsorption performance and structural stability of the material, avoiding performance defects caused by uneven distribution of components, providing a homogeneous material basis for subsequent molding processing, and ensuring the consistency and reliability of product performance. The twin-screw extruder is set at a temperature of 170-190℃, a pressure of 6-10MPa, and a time of 5-10 minutes, so that the re-mixed materials are further plasticized, homogenized and compacted under suitable thermomechanical conditions, promoting close bonding and molecular chain entanglement between the components, improving the rheological properties and molding processability of the material, ensuring the continuity and stability of extrusion molding, and improving the density and mechanical properties of the carbon-based core material, so that it can meet higher quality standards and application requirements. The water-cooled forming system adopts multi-nozzle spray water cooling, and the extruded sheet is quickly and evenly cooled at a water pressure of 0.3-0.5MPa, a water temperature of 10-20℃ and a cooling rate of 50-80℃ / s. Rapid cooling can quickly solidify the material and maintain the good microstructure and shape accuracy formed during the extrusion process, inhibit the relaxation and crystallization behavior of the macromolecular chain, thereby improving the strength, hardness and dimensional stability of the material, reducing thermal deformation and internal stress, and improving the appearance quality and performance of the product, providing high-quality carbon-based core material semi-finished products for subsequent processing and application.

[0020] In the preparation method of the material of the present invention, the adhesive preparation step is carried out through a series of fine treatments such as precise proportion selection of various raw materials, staged preheating and premixing, multi-speed stirring, vacuum degassing and filter filtration, so that the various components are fully and evenly mixed, bubbles and impurities are effectively eliminated, and the curing performance is optimized, thereby preparing a water-based environmentally friendly heterogeneous adhesive with high adhesion, low volatile organic compound emissions and stable performance, ensuring that the technological veneer and the carbon-based core material are firmly bonded, improving the overall performance and environmental quality of the material, and meeting the production needs of high-quality products.

[0021] Preferably, the preparation method of the carbon-based lightweight energy-saving material for technological wood veneer in step S22 comprises the following specific operations: taking 40-60 parts of aqueous polyurethane dispersion, 20-40 parts of acrylic emulsion, 10-20 parts of polyisocyanate curing agent, 5-10 parts of epoxy curing agent, 0.1-0.5 parts of defoaming agent, and 0.5-2 parts of thickener according to the proportion; preheating the aqueous polyurethane dispersion and acrylic emulsion at 40-50°C for 15-20 minutes; The curing agent is premixed in a dry nitrogen atmosphere at 25-30°C for 10-15 minutes; the preheated adhesive raw materials are mixed and stirred at a low speed of 300-400r / min for 30-60 seconds, and then increased to 800-1000r / min and stirred for 20-30 minutes; the stirred adhesive is transferred to a vacuum degassing tank and degassed at a vacuum degree of -0.08 to -0.1MPa for 10-15 minutes; the degassed adhesive is filtered through a 150-200 mesh filter to remove impurities and undissipated bubbles.

[0022] 40-60 parts of waterborne polyurethane dispersion and 20-40 parts of acrylic emulsion are mixed in proportion. The good flexibility, wear resistance, water resistance of waterborne polyurethane dispersion and the excellent weather resistance, adhesion and other properties of acrylic emulsion are combined to make the adhesive have a variety of excellent properties to meet the requirements for material performance in different use environments.

[0023] The addition of 10-20 parts of polyisocyanate curing agent and 5-10 parts of epoxy curing agent can cause cross-linking reaction with waterborne polyurethane dispersion and acrylic emulsion through appropriate amount of curing agent, thereby increasing the cross-linking density of the adhesive, thereby significantly enhancing the cohesion, adhesion, heat resistance, chemical resistance and other properties of the adhesive, ensuring that the adhesive can maintain good bonding effect during use.

[0024] The addition of a small amount of 0.1-0.5 parts of defoamer can effectively eliminate bubbles generated during the preparation and use of the adhesive, avoiding the negative impact of bubbles on the bonding effect and material properties; the appropriate addition of 0.5-2 parts of thickener can adjust the viscosity of the adhesive, giving it good coating performance and leveling properties, facilitating construction operations, and also helping to improve the storage stability of the adhesive.

[0025] At the same time, the waterborne polyurethane dispersion and acrylic emulsion are preheated at 40-50°C for 15-20 minutes. Preheating can reduce the viscosity of the material, improve the molecular mobility, make the two emulsions easier to merge with each other during the subsequent mixing and stirring process, promote the diffusion and entanglement between molecules, ensure more uniform mixing, and improve the performance consistency and stability of the adhesive. The polyisocyanate curing agent and the epoxy curing agent are premixed at a lower temperature of 25-30°C and a dry nitrogen atmosphere for 10-15 minutes to prevent the curing agent from reacting with impurities such as moisture in the air and affecting its activity. At the same time, the appropriate temperature and time can make the curing agent fully mixed and uniform, ensuring that it can be evenly dispersed and effectively participate in the cross-linking reaction when mixed with other raw materials later.

[0026] When stirring, stir at a low speed of 300-400r / min for 30-60 seconds to pre-mix the various raw materials after preheating, avoid splashing of materials or local overheating due to large shear force generated at the beginning of high-speed stirring, and lay the foundation for subsequent high-speed stirring and mixing, so that the raw materials begin to contact and merge under relatively mild conditions. Then increase the high-speed stirring to 800-1000r / min to produce strong shear force, so that the raw materials are fully mixed and evenly dispersed at the molecular level, promote the chemical reaction between water-based polyurethane dispersion, acrylic emulsion and curing agent, and improve the degree and uniformity of cross-linking reaction, thereby further optimizing the performance of adhesive. Degassing treatment is carried out at a vacuum degree of -0.08 to -0.1MPa to effectively remove the air mixed into the adhesive during stirring and the bubbles generated by the reaction, and avoid the formation of pores or defects in the bubbles after the adhesive is cured, thereby improving the bonding strength, density and appearance quality of the adhesive, and ensuring the sealing and reliability of the bonding part. After degassing, the adhesive is filtered through a 150-200 mesh filter to effectively intercept foreign particles, incompletely dissolved solid components, and undissipated tiny bubbles in the adhesive, further improving the purity and quality of the adhesive, preventing impurities from having adverse effects on the bonding effect and material properties, and ensuring the stability and reliability of the adhesive during use.

[0027] In the preparation method of the material of the present invention, the pre-pressing step of the assembly makes the material body initially compacted, the air is discharged, the density and performance consistency are improved through reasonable pressure, pressure increase rate, pre-pressing time, zone pressure regulation and appropriate temperature and humidity control, while providing a stable and good-quality body for subsequent processing, thereby ensuring the overall quality of the carbon-based lightweight and energy-saving material of the scientific and technological wood veneer.

[0028] Preferably, the specific operation of pre-pressing the pre-pressing machine in step S24 of the method for preparing the technological wood veneer carbon-based lightweight energy-saving material includes: the pre-pressing machine pressure is stabilized at 0.4-0.6MPa, the pressure increase rate is 0.05-0.1MPa / s, the pre-pressing time is controlled at 5-10 minutes, the pre-pressing machine plate adopts a zoned pressure regulation design, and the pressure is independently controlled in 3-5 zones according to the material size and structural characteristics, the ambient temperature is controlled at 20-25°C, and the humidity is maintained at 40-50%.

[0029] The pressure is stable at 0.4-0.6MPa. The appropriate pressure can make the components in the blank closely combined, improve the density and integrity of the material, enhance the mechanical strength of the material, make it less likely to deform and damage in subsequent use, and also help improve the thermal conductivity, electrical conductivity and other physical properties of the material. The slow and stable pressure increase rate of 0.05-0.1MPa / s allows the air inside the material to have enough time to be discharged, avoiding the air being trapped in the blank to form pores or bubbles due to excessive pressure increase, thereby ensuring the uniformity and quality stability of the material and reducing the occurrence of internal defects. A sufficient pre-pressing time of 5-10 minutes can ensure that the material is fully deformed and compacted under pressure, making the combination between the components more firm, further improving the density and performance uniformity of the material, and also conducive to the uniform distribution of stress inside the material, reducing the risk of deformation during subsequent processing and use.

[0030] The zoned pressure regulation design is based on the material size and structural characteristics, and the pressure is independently controlled in 3-5 zones. This can apply more precise pressure to different areas, adapt to the structural differences and force requirements of materials in different parts, avoid deformation, cracking and other problems caused by excessive or insufficient pressure in certain areas due to overall pressure, and improve the quality and performance consistency of the material.

[0031] The ambient temperature is controlled at 20-25℃, which is conducive to the stable chemical reaction in the material such as curing reaction, and avoids the adverse effect of too high or too low temperature on the material performance. Too high temperature will cause the material to cure prematurely and the performance will decrease, while too low temperature will cause incomplete reaction and insufficient material strength, etc. It also helps to maintain the dimensional stability of the material and reduce deformation caused by thermal expansion and contraction. The humidity is maintained at 40-50%. The appropriate humidity environment can prevent the material from being too dry and cracking during the pre-pressing process or being too wet and affecting the material's performance and bonding strength, which helps to maintain the physical and chemical stability of the material and ensure that the material's performance after pre-pressing reaches the best state.

[0032] The three-stage operation of the cold pressing and curing step in the preparation method of the material of the present invention controls the specific pressure, pressure increase and decrease rate, platen displacement, temperature and humidity in each stage, so that the material can achieve a tight and stable internal structure, uniform stress release, and sufficient and appropriate chemical reaction during the compaction, curing, and cooling and pressure relief processes, thereby improving the strength, density, durability, dimensional stability and overall performance quality of the material and ensuring that the product meets the expected high standards.

[0033] Preferably, the cold pressing and curing in step S25 of the preparation method of the technological wood veneer carbon-based lightweight energy-saving material is a three-stage operation, specifically including: 0-0.5h is the rapid compaction stage, the pressure is set to 1.5-2.0MPa, the pressure is rapidly increased at a rate of 0.4-0.6MPa / min, the displacement of the cold press plate is controlled at 0.5-1.0mm / min, and the ambient temperature is maintained at 20-22°C and the humidity is 45-50%; 0.5-2.5h is the stable curing stage, the pressure is stabilized at 1.2-1.5MPa, the temperature is controlled at 22-24°C, and the humidity is constant at 48-52%; 2.5-3.5h is the cooling and pressure relief stage, the pressure is linearly reduced to 0-0.3MPa, the pressure reduction rate is 0.1-0.2MPa / h, and the cooling system is started simultaneously to cool to 15-18°C at a rate of 5-8°C / h.

[0034] The pressure of the rapid compaction stage of 0-0.5h is set to 1.5-2.0MPa, and the pressure increase rate is 0.4-0.6MPa / min. The higher pressure and faster pressure increase rate enable the material to be compacted quickly in a short time, expel more air and moisture, make the internal structure of the material more compact, improve the density and strength of the material, reduce the porosity, and lay a good foundation for subsequent curing. By controlling the displacement speed of the pressing plate at 0.5-1.0mm / min, the material is ensured to be evenly compressed during the compaction process, and the deformation or uneven performance of the material caused by excessive or insufficient local pressure is avoided, so as to ensure the quality stability of the material. The ambient temperature is maintained at 20-22℃ and the humidity is 45-50%. The appropriate temperature and humidity conditions are conducive to the material maintaining good physical and chemical properties during the compaction process, and avoiding excessively high or low temperature, excessive or insufficient humidity, which have adverse effects on the material structure and performance. Excessive temperature will cause the material to solidify prematurely or the performance will decline, and excessive humidity will affect the bonding performance of the material. The pressure is stable at 1.2-1.5MPa during the stable curing stage of 0.5-2.5h. Maintaining a relatively stable and moderate pressure during this stage helps the chemical reaction inside the material to continue to proceed stably, further solidify and stabilize the material, and improve the material's strength, hardness, durability and other properties. The temperature is controlled at 22-24℃ and the humidity is constant at 48-52%, which provides an ideal environment for the curing reaction of the material. The increase in temperature is conducive to accelerating the curing reaction, but too high a temperature will lead to a decrease in material performance. Therefore, controlling it within an appropriate range can ensure that the curing reaction is fully carried out and the material performance is good; stable humidity can ensure that the material will not be affected by excessive or insufficient moisture during the curing process. The curing effect and performance.

[0035] During the 2.5-3.5h cooling and decompression stage, the pressure drops linearly to 0-0.3MPa, with a decompression rate of 0.1-0.2MPa / h. The slow decompression gradually releases the internal stress of the material, avoiding problems such as internal stress concentration, deformation or cracking caused by a sudden drop in pressure, and ensuring the dimensional stability and integrity of the material. The cooling system is started synchronously, and cooling at a rate of 5-8℃ / h helps the material maintain structural stability during the cooling process, avoids thermal stress and deformation caused by rapid temperature changes, stabilizes the material at a lower temperature, and further improves the performance and quality stability of the material.

[0036] The present invention provides a cabinet door panel product made of carbon-based lightweight energy-saving material with a technological wood veneer, which combines the aesthetics of the technological wood veneer with the characteristics of the carbon-based lightweight energy-saving material. It can not only provide a beautiful and natural wood decorative effect for furniture, and enhance the decorative quality and artistic value of the product, but also utilize the lightweight characteristics of the carbon-based material to facilitate installation and use. At the same time, its energy-saving performance helps to reduce energy consumption, meets the requirements of environmental protection and sustainable development, and provides the furniture industry with a high-performance, multi-functional and environmentally friendly new cabinet door panel material option.

[0037] The present invention provides a cabinet door panel product made of carbon-based light-weight energy-saving material with a technological wood veneer. The cabinet door panel product is made from the technological wood veneer carbon-based light-weight energy-saving material.

[0038] This cabinet door panel product made of carbon-based lightweight energy-saving materials with technological wood veneer has many functions. The technological wood veneer can simulate the texture and color of various natural woods, making the cabinet door panel have a realistic wooden appearance, enhancing the overall beauty and decorative effect of the furniture, meeting consumers' needs for different styles and textures, and adding a natural and warm atmosphere to the home environment; the application of carbon-based lightweight energy-saving materials makes the cabinet door panel lighter, easier to carry, install and use in daily life, reduces labor intensity and installation difficulty, and also reduces the overall weight of the furniture, making it easier to move and adjust the layout, and improving the convenience of use; carbon-based materials have Good thermal insulation, heat preservation or other special energy-saving properties can help reduce the transfer of indoor and outdoor heat, reduce energy consumption, achieve energy conservation and emission reduction, and meet the requirements of modern environmental protection concepts and sustainable development; the material has a certain strength and stability, and can provide good structural support for the cabinet door panel, making it not easy to deform or damage, extending the service life, and ensuring the normal use function and safety of the furniture; according to specific needs, the material can be functionally modified or designed to add antibacterial, fireproof, moisture-proof and other functions, so that the cabinet door panel has a variety of special functions to meet the requirements of different usage scenarios and environments, and improve the added value and market competitiveness of the product.

[0039] In summary, the present invention has the following beneficial effects: 1. The carbon-based lightweight energy-saving material for technological wood veneer provided by the present invention has multiple components, and the raw materials in the formula are synergistically effective. The core raw materials are taken from the residues of bamboo processing. The use of bamboo charcoal powder, bamboo activated carbon powder and bamboo powder realizes resource circulation, effectively alleviates the shortage of wood resources, reduces costs, and improves utilization efficiency, which is in line with the concept of environmental protection development; bamboo charcoal and activated carbon powder complement each other to build a powerful purification system, bamboo powder enhances mechanical properties, thermoplastic polymer masterbatch guarantees processability, processing auxiliary materials optimize the process, and various components synergize to achieve the integration of light weight and high strength of materials, adsorption purification and convenient processing; technological wood veneer simulates natural texture and color to enrich decoration, water-based environmentally friendly heterogeneous adhesives are formulated in a specific proportion, multiple curing agents synergistically improve adhesion, and use the water-based system to reduce volatile organic compounds. Defoamers and thickeners optimize processing performance, ensure that the veneer and core material are firmly bonded, and comprehensively improve structural stability and environmental quality, laying a solid performance foundation for the product; 2. As for the overall preparation process of the technological wood veneer carbon-based lightweight energy-saving material of the present invention, starting from ingredient weighing and baking preheating, it undergoes high-speed stirring, melt granulation, re-mixing and molding until post-processing, and the parameters of each link are precisely controlled; high-speed stirring ensures uniform distribution of materials, melt granulation accurately regulates particle size and temperature, re-mixing and molding optimizes the inherent structural performance of materials, and post-processing strictly guarantees the quality of finished products, comprehensively improves production efficiency and product qualification rate, and stabilizes the consistency and stability of material performance; in terms of adhesive formulation, the raw materials undergo multi-stage pretreatment such as emulsion preheating and curing agent premixing, combined with multi-speed stirring, vacuum degassing and filter filtration operations, deeply optimizes the adhesive product Quality, effectively remove bubble impurities, improve the curing reaction process, strengthen adhesion, reduce volatile organic compound emissions, strongly ensure strong and reliable bonding, excellent environmental performance, and create key support for product quality; as for the molding process, pre-pressing and cold pressing curing accurately set the pressure, pressure increase and decrease rate, platen displacement and temperature and humidity parameters according to the characteristics of the material, pre-pressing and compacting the blank, evacuating the internal air, and balancing the performance; cold pressing curing uses a three-stage operation to make the material structure dense and stable, the stress release is stable, and the curing is uniform and sufficient, which greatly improves the material strength, density, durability and dimensional stability, helps the product to successfully meet the expected high standards and comprehensively guarantee the comprehensive quality level of the product; 3. The invention has significant advantages over traditional materials. In terms of resource sustainability, it breaks through the scarcity of solid wood, relies on bamboo processing residues to achieve resource recycling, and builds a stable supply model, which is far superior to traditional solid wood, and lays a solid foundation for the long-term development of the industry; in terms of environmental health, it greatly reduces formaldehyde release by taking advantage of the strong adsorption of bamboo charcoal activated carbon and the environmental protection characteristics of water-based adhesives, purifies the air from the source and throughout the use process, and significantly improves the indoor environment, which is superior to traditional artificial boards such as density boards and particle boards with excessive formaldehyde, ensuring healthy use; in terms of comprehensive performance, it overcomes the problem of easy deformation and cracking of solid wood, and strengthens strength and toughness by combining raw materials and improving processes, and has both light weight and energy-saving characteristics, making up for the defects of traditional boards that are heavy and have high energy consumption; 4. The cabinet door panel products made of carbon-based light-weight energy-saving materials with technological wood veneer of the present invention integrate excellent characteristics such as light weight, high strength, heat insulation, low formaldehyde release and various decorations. Its core raw materials and preparation process are exquisitely coordinated, and the microstructure is dense and tough, which can effectively resist external forces, wear and tear, and temperature and humidity stress. The cabinet door panel maintains a precise shape and a stable structure for a long time, and has excellent durability. The maintenance and cost are greatly reduced, the life span is significantly extended, and the handling and installation are easy and free. The manpower and material costs are significantly reduced, and the efficiency is increased. The furniture layout can be changed at will, and it can flexibly meet the diverse life and space creativity needs; in terms of heat insulation, the cabinet door panel products made of this material are unique. Special ingredients and micro-optimization work together to strongly cut off heat conduction, significantly slow down indoor and outdoor heat exchange, maintain constant indoor temperature and humidity, improve living comfort, sharply reduce HVAC energy consumption, and achieve significant energy-saving and carbon-reduction results. At the same time, formaldehyde control in the preparation process of the material cabinet door panel products is extremely strict, raw material screening prevents source release, and the entire preparation process is closely monitored. The formaldehyde content of the finished product is far lower than the international standard. The cabinet door panel products made of this material have diverse decorative characteristics, and the technological wood veneer uses cutting-edge technology and artistic ingenuity to realistically simulate the delicate texture and rich color changes of various natural woods, satisfying personalized aesthetic pursuits while achieving diversified functional expansion. DETAILED DESCRIPTION

[0040] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

[0041] Example 1

[0042] S1 carbon-based core material preparation: S11 Ingredient weighing: accurately weigh 25 parts of bamboo charcoal powder, 5 parts of bamboo activated carbon powder, 10 parts of bamboo powder, 40 parts of thermoplastic polymer masterbatch, and 1 part of processing auxiliary material, and pre-bake and heat each material component for 1 hour; S12 high-speed stirring: put the weighed bamboo charcoal powder, bamboo powder, thermoplastic polymer masterbatch and processing auxiliary materials into a high-speed mixer, and stir continuously at 1200r / min for 5 minutes to ensure that the materials are evenly mixed; S13 melt granulation: the uniformly stirred mixture is transferred to a twin-screw extruder, wherein the feeding section is 160°C, the compression section is 175°C, the metering section is 180°C, the die pressure is set to 12MPa, the rotation speed is 200r / min, the mixture is melt-blended, and granulated after extrusion, and the particle size is controlled to be 10 mesh; S14: mixing and molding again: first, the obtained particles are stirred in a high-speed mixer at a speed of 1300r / min for 30 seconds, then the bamboo activated carbon powder after high-temperature carbonization is added, and stirring is continued for 1 minute, and then the mixture is put into a twin-screw extruder for melt blending and extrusion, the temperature is 170°C, the pressure is 6MPa, the time is 5 minutes, a plate-shaped extrusion die is used, and water cooling molding is performed after extrusion, the water pressure is 0.3MPa, the water temperature is 10°C, and the cooling rate is 50°C / s. S15 post-processing: Cut the cooled and shaped plates into the standard size required for production, inspect the plates with multiple indicators, and obtain qualified carbon-based core materials for standby use; S2 technology wood veneer processing and compounding: S21 veneer preparation: Dry the technical wood veneer to a moisture content of 8%, pre-bake at 60°C for 2 hours, and cut it into the same size as the carbon-based core material; S22 adhesive preparation: 40 parts of waterborne polyurethane dispersion, 20 parts of acrylic emulsion, 10 parts of polyisocyanate curing agent, 5 parts of epoxy curing agent, 0.1 parts of defoaming agent, and 0.5 parts of thickener are prepared into waterborne environmentally friendly heterogeneous adhesive according to the proportion, stirred at room temperature for 20 minutes at 800r / min, and vacuum degassed at -0.08MPa for 10 minutes. After degassed, the adhesive is filtered through a 150-mesh filter to remove impurities and undissipated bubbles; S23 Uniform Gluing: Apply glue evenly to the surface, and the glue amount is controlled at 70g / ㎡; S24 pre-pressing of the assembly: After the adhesive coating surface and the carbon-based core material surface are precisely fitted, they are quickly sent into the pre-pressing machine with a zoned pressure adjustment design and lightly pressed at a pressure of 0.4MPa for 5 minutes; S25 cold pressing and curing: The carbon-based core material and technological wood veneer composite with precise bonding on the glue-coated surface are then transferred to the cold press, and a three-stage cold pressing is adopted. The ambient temperature is controlled at 15°C and the humidity is 40% throughout the process. 0-0.5h is the rapid compaction stage, the pressure is set to 1.5MPa, and the displacement of the cold press plate is controlled at 0.5mm / min. At the same time, the ambient temperature is maintained at 20°C and the humidity is 45%; 0.5-2.5h is the stable curing stage, the pressure is stabilized at 1.2MPa, the temperature is controlled at 22°C, and the humidity is constant at 48%; 2.5-3.5h is the cooling and pressure relief stage, the pressure drops linearly to 0MPa, and the cooling system is started simultaneously to cool down to 17°C at a rate of 5°C / h to obtain the composite technological wood veneer carbon-based lightweight energy-saving material.

[0043] Example 2

[0044] S1 carbon-based core material preparation: S11 Ingredient weighing: accurately weigh 60 parts of bamboo charcoal powder, 15 parts of bamboo activated carbon powder, 20 parts of bamboo powder, 70 parts of thermoplastic polymer masterbatch, and 10 parts of processing auxiliary materials, and pre-bake and heat each material component for 2 hours; S12 high-speed stirring: put the weighed bamboo charcoal powder, bamboo powder, thermoplastic polymer masterbatch and processing auxiliary materials into a high-speed mixer, and stir continuously at 1500r / min for 10 minutes to ensure that the materials are evenly mixed; S13 melt granulation: the uniformly stirred mixture is transferred to a twin-screw extruder, wherein the feeding section is 170°C, the compression section is 185°C, the metering section is 190°C, the die pressure is set to 18 MPa, the rotation speed is 300 r / min, and the mixture is melt-blended, extruded and granulated, and the particle size is controlled to be 20 mesh; S14: mixing and molding again: first, the obtained particles are stirred in a high-speed mixer at a speed of 1500r / min for 60 seconds, then the bamboo activated carbon powder after high-temperature carbonization is added, and stirring is continued for 2 minutes, and then the mixture is put into a twin-screw extruder for melt blending and extrusion, the temperature is 190°C, the pressure is 10MPa, the time is 10 minutes, a plate-shaped extrusion die is used, and water cooling molding is performed after extrusion, the water pressure is 0.5MPa, the water temperature is 20°C, and the cooling rate is 80°C / s. S15 post-processing: Cut the cooled and shaped plates into the standard size required for production, inspect the plates with multiple indicators, and obtain qualified carbon-based core materials for standby use; S2 The processing and compounding steps of the technological wood veneer are the same as those in Example 1 to obtain the composite technological wood veneer carbon-based lightweight energy-saving material.

[0045] Example 3

[0046] S1 Carbon-based core material preparation All operations are the same as in Example 1; S2 technology wood veneer processing and compounding: S21 veneer preparation: Dry the technical wood veneer to a moisture content of 12%, pre-bake at 80℃ for 4 hours, and cut into the same size as the carbon-based core material; S22 adhesive preparation: 60 parts of waterborne polyurethane dispersion, 40 parts of acrylic emulsion, 20 parts of polyisocyanate curing agent, 10 parts of epoxy curing agent, 0.5 parts of defoaming agent, and 2 parts of thickener are mixed into a waterborne environmentally friendly heterogeneous adhesive according to the proportion, stirred at room temperature for 30 minutes at 1000r / min, and vacuum degassed at -0.1MPa for 15 minutes. After degassed, the adhesive is filtered through a 200-mesh filter to remove impurities and undissipated bubbles; S23 Uniform Gluing: Apply glue evenly to the surface, and the glue amount is controlled at 130g / ㎡; S24 pre-pressing of the assembly: After the adhesive coating surface and the carbon-based core material surface are precisely fitted, they are quickly sent to the pre-pressing machine with a zoned pressure adjustment design and lightly pressed at a pressure of 0.6MPa for 10 minutes; S25 cold pressing and curing: The carbon-based core material and the high-tech wood veneer composite with precise bonding on the glue-coated surface are then transferred to the cold press, and a three-stage cold pressing is adopted. The ambient temperature is controlled at 25°C and the humidity is 60% throughout the process. 0-0.5h is the rapid compaction stage, the pressure is set to 2.0MPa, and the displacement of the cold press plate is controlled at 1.0mm / min. At the same time, the ambient temperature is maintained at 22°C and the humidity is 50%; 0.5-2.5h is the stable curing stage, the pressure is stabilized at 1.5MPa, the temperature is controlled at 24°C, and the humidity is constant at 52%; 2.5-3.5h is the cooling and pressure relief stage, the pressure drops linearly to 0.3MPa, and the cooling system is started simultaneously to cool down to 16°C at a rate of 8°C / h to obtain the composite carbon-based lightweight energy-saving material with high-tech wood veneer.

[0047] Comparative Example 1 S1 Carbon-based core material preparation All operations are the same as in Example 1; S2 Bamboo veneer finishing and lamination: S21 veneer preparation: dry the bamboo skin to a moisture content of 12%, pre-bake at 80℃ for 4 hours, and cut into the same size as the carbon-based core material; S22 adhesive preparation: 40 parts of waterborne polyurethane dispersion, 20 parts of acrylic emulsion, 10 parts of polyisocyanate curing agent, 5 parts of epoxy curing agent, 0.1 parts of defoaming agent, and 0.5 parts of thickener are prepared into waterborne environmentally friendly heterogeneous adhesive according to the proportion, stirred at room temperature for 20 minutes at 800r / min, and vacuum degassed at -0.08MPa for 10 minutes. After degassed, the adhesive is filtered through a 150-mesh filter to remove impurities and undissipated bubbles; S23 Uniform Gluing: Apply glue evenly to the surface, and the glue amount is controlled at 70g / ㎡; S24 pre-pressing of the assembly: After the adhesive coating surface and the carbon-based core material surface are precisely fitted, they are quickly sent into the pre-pressing machine with a zoned pressure adjustment design and lightly pressed at a pressure of 0.4MPa for 5 minutes; S25 cold pressing and curing: The carbon-based core material and bamboo skin composite with precise adhesive surface fitting are then transferred to the cold press, which adopts three-stage cold pressing. The ambient temperature is controlled at 15℃ and the humidity is 40% throughout the process. 0-0.5h is the rapid compaction stage, the pressure is set to 1.5MPa, and the displacement of the cold press plate is controlled at 0.5mm / min. At the same time, the ambient temperature is maintained at 20℃ and the humidity is 45%; 0.5-2.5h is the stable curing stage, the pressure is stabilized at 1.2MPa, the temperature is controlled at 22℃, and the humidity is constant at 48%; 2.5-3.5h is the cooling and pressure relief stage, the pressure drops linearly to 0MPa, and the cooling system is started simultaneously to cool down to 17℃ at a rate of 5℃ / h to obtain the composite bamboo skin veneer carbon-based cabinet door panel material.

[0048] Comparative Example 2 S1 Carbon-based core material preparation All operations are the same as in Example 1; S2 impregnated paper finishing and lamination: S21 facing preparation: dry the impregnated paper to a moisture content of 12%, pre-bake at 80°C for 4 hours, and cut into the same size as the carbon-based core material; S22 adhesive preparation: 40 parts of waterborne polyurethane dispersion, 20 parts of acrylic emulsion, 10 parts of polyisocyanate curing agent, 5 parts of epoxy curing agent, 0.1 parts of defoaming agent, and 0.5 parts of thickener are prepared into waterborne environmentally friendly heterogeneous adhesive according to the proportion, stirred at room temperature for 20 minutes at 800r / min, and vacuum degassed at -0.08MPa for 10 minutes. After degassed, the adhesive is filtered through a 150-mesh filter to remove impurities and undissipated bubbles; S23 Uniform Gluing: Apply glue evenly to the surface, and the glue amount is controlled at 70g / ㎡; S24 pre-pressing of the assembly: After the adhesive coating surface and the carbon-based core material surface are precisely fitted, they are quickly sent into the pre-pressing machine with a zoned pressure adjustment design and lightly pressed at a pressure of 0.4MPa for 5 minutes; S25 cold pressing and curing: The carbon-based core material and impregnated paper composite with precise adhesive surface fitting are then transferred to the cold press, and three-stage cold pressing is adopted. The ambient temperature is controlled at 15°C and the humidity is 40% throughout the process. 0-0.5h is the rapid compaction stage, the pressure is set to 1.5MPa, and the displacement of the cold press plate is controlled at 0.5mm / min. At the same time, the ambient temperature is maintained at 20°C and the humidity is 45%; 0.5-2.5h is the stable curing stage, the pressure is stabilized at 1.2MPa, the temperature is controlled at 22°C, and the humidity is constant at 48%; 2.5-3.5h is the cooling and pressure relief stage, the pressure drops linearly to 0MPa, and the cooling system is started simultaneously to cool down to 17°C at a rate of 5°C / h to obtain the composite impregnated paper veneer carbon-based cabinet door panel material.

[0049] Comparative Example 3 S1 Carbon-based core material preparation The various operations are prepared to obtain a bamboo charcoal board for cabinet door panels.

[0050] Take the carbon-based lightweight energy-saving materials with technological wood veneer of Examples 1-3 and the cabinet door panel materials of Comparative Examples 1-3 of the same specifications, and test the physical and chemical indicators of moisture content, flexural strength, flexural elastic modulus, dimensional stability and water absorption thickness expansion rate of each material. The results are shown in Table 1.

[0051] Table 1 Test results of material properties of each group

[0052] Result analysis: From the performance comparison table data results of each technological wood veneer carbon-based lightweight energy-saving material and each cabinet door panel material of Examples 1-3 and Comparative Examples 1-3, it can be seen that the flexural strength of Examples 1-3 is in the range of 27.3-27.7MPa, which is due to the stable support frame constructed by bamboo charcoal powder, bamboo activated carbon powder and bamboo powder and the effective bonding enhancement of thermoplastic polymer masterbatch, which are all higher than Comparative Examples 1-3; among them, the flexural strength of the bamboo skin veneer material of Comparative Example 1 is 26.6MPa, the flexural strength of the impregnated paper veneer material of Comparative Example 2 is only 25.1MPa, and the flexural strength of the pure bamboo charcoal board of Comparative Example 3 is 25.3MPa. Due to the lack of optimized compounding or poor surface adaptation, the stress transfer and dispersion of the comparative examples are weak, and the bearing capacity is limited, which affects the furniture's bearing of heavy objects and long-term structural stability. Therefore, the flexural strength of each technological wood veneer carbon-based lightweight energy-saving material in the embodiments has significant advantages.

[0053] The flexural elastic modulus of the carbon-based lightweight energy-saving materials with technological wood veneers in Examples 1-3 of the present invention are all between 4580 and 4690 MPa. The high modulus reflects that the materials have strong resistance to bending deformation, a tight and orderly microstructure, and strong atomic bonding force; while the flexural elastic modulus of Comparative Example 1 is 4290 MPa, that of Comparative Example 2 is 3810 MPa, and that of Comparative Example 3 is 3940 MPa. The lower modulus makes the materials in the comparative examples easy to bend and deform, and the cabinet doors are prone to drooping and losing flatness during use, and cannot meet the requirements of high-precision assembly and frequent opening and closing stability. Therefore, the charcoal-based lightweight energy-saving materials with technological wood veneers in the embodiments of the present invention have advantages in maintaining shape accuracy and ensuring performance.

[0054] When the dimensional stability index is tested, the thickness growth rate of Examples 1-3 is 1.00%-1.01%, and the shrinkage rate is 0.20%-0.22%. This is due to the precise material composite process, the coordinated optimization of the microstructure by multiple components, and the fine control of temperature and pressure during processing to reduce thermal stress and uneven shrinkage; while the thickness growth rate of Comparative Example 1 is 0.77%, and the shrinkage rate is 0.22%. The bamboo skin properties and the composite process limitations cause changes, affecting the tightness of the cabinet door closure; Comparative Example 2 increases by 1.27% and shrinks by 1.04%, and the water absorption characteristics of the impregnated paper cause large fluctuations, damaging the structure and appearance; Comparative Example 3 has a growth rate of 1.00% and a shrinkage rate of 0.40%. The stability of the single structure is weaker than that of the embodiment, affecting the furniture assembly and long-term dimensional accuracy. Therefore, the present invention The embodiments ensure constant size, improve user experience and product life; at the same time, the length growth rate of embodiments 1-3 is 0.09%-0.11%, and the shrinkage rate is 0.19%-0.21%. The material has good isotropy and the process balances the internal stress well; the comparative example 1 grows by 0.61% and shrinks by 0.21%. The anisotropy of the bamboo skin and the insufficient process cause length fluctuations, which interfere with the layout and function of the furniture; the comparative example 2 grows by 0.01% and shrinks by 0.11%. Although the impregnated paper shrinks little, it has weak synergy with the core material, affecting the overall stability; the comparative example 3 grows by 0.19% and shrinks by 0.05%. The length stability of a single bamboo charcoal board is not good. Therefore, the various technological wood veneer carbon-based lightweight energy-saving materials of the embodiments of the present invention have all-round stable size, strengthened structure, and expanded application adaptability.

[0055] In addition, the water absorption thickness expansion rate of the technological wood veneer carbon-based lightweight energy-saving materials of Examples 1-3 is 0.35%-0.40%, and the pore structure of components such as bamboo charcoal powder is optimized and waterproofed, and the adhesive has a dense barrier to prevent water intrusion; while the water absorption thickness expansion rate of the bamboo skin veneer in Example 1 is 0.50%, the bamboo skin has strong water absorption and weak protection, and water intrusion causes expansion and deformation, delamination and degumming, which endangers the structural integrity and decorativeness; the impregnated paper test of Example 2 fell off and no data could be obtained, and the serious water absorption and expansion made it impossible to withstand the test, seriously affecting the moisture resistance; the water absorption thickness expansion rate of the bamboo charcoal board in Example 3 is 0.40%, and the lack of decorative protection makes it easy to absorb water and expand. Therefore, the technological wood veneer carbon-based lightweight energy-saving materials in the embodiments of the present invention rely on material composite and process innovation to effectively waterproof and moisture-proof, improve durability, broaden the range of use environment, and enhance market competitiveness.

[0056] In summary, the carbon-based lightweight energy-saving materials of the technological wood veneers in the embodiments of the present invention are synergistically improved through bamboo charcoal powder, activated carbon powder, bamboo powder and polymer masterbatch to improve the comprehensive performance. The adsorption purification, structural enhancement and polymer processability of bamboo charcoal-based materials are combined to improve the functional structure, which exceeds that of a single material or a simple combination; the composite of the technological wood veneers in Examples 1-3 has excellent moisture-proof performance, enhanced material structure, and diverse decorative functions, and the water-based environmentally friendly heterogeneous adhesive is suitable for the gluing process; the bamboo skin of Comparative Example 1 and the impregnated paper veneer of Comparative Example 2 are weak in performance integration, the impregnated paper absorbs water and falls off, and the stability and strength of the bamboo skin are poor. Therefore, the composite of the technological wood veneers in the materials of the present invention has significant adaptability and functional advantages.

[0057] The embodiment of the composited technological wood veneer carbon-based lightweight energy-saving material obtained by the present invention has precise control of parameters in each link of the preparation process, from carbon-based core material formulation to veneer composite, quality control to improve performance, precise operations such as melt granulation, mixing molding, and adhesive formulation to ensure material uniformity, stability and adhesion. The comparative example cannot reach the performance level of the embodiment due to process differences or simplifications, which fully illustrates that the preparation process innovation of the technological wood veneer carbon-based lightweight energy-saving material of the present invention is the key to the high performance and high quality of the technological wood veneer carbon-based lightweight energy-saving material and its cabinet door panel products, supporting the improvement of product competitiveness and application potential in the market.

Claims

1. A carbon-based lightweight energy-saving material for technological wood veneer, characterized in that: Its material composition includes carbon-based core material and technological wood veneer; the carbon-based core material includes 25-60 parts of bamboo charcoal powder, 5-15 parts of bamboo activated carbon powder, 10-20 parts of bamboo powder, 40-70 parts of thermoplastic polymer masterbatch, and 1-10 parts of processing auxiliary materials; the technological wood veneer includes technological wood veneer and water-based environmentally friendly heterogeneous adhesive.

2. The carbon-based lightweight energy-saving material for technological wood veneer according to claim 1 is characterized in that: The bamboo charcoal powder in the carbon-based core material has a carbonization temperature of 500-800°C, a density of 0.6-0.8g / cm³, an ash content of 0.5-3%, a specific surface area of ​​250-350m² / g, and a particle size of 60-325 meshes, and is derived from the pyrolysis of bamboo processing residues; the bamboo activated carbon powder is a bamboo charcoal activation product, has a specific surface area of ​​50-150m² / g, and an average pore size of 2-4nm; the particle size of the bamboo powder is 50-60 meshes; the thermoplastic polymer masterbatch is a thermoplastic resin; and the processing auxiliary materials include lubricants such as stearic acid and release agents.

3. The carbon-based lightweight energy-saving material for technological wood veneer according to claim 1 is characterized in that: The water-based environmentally friendly heterogeneous adhesive in the technological wood veneer is compatible with the technological wood veneer and the carbon-based core material. The water-based environmentally friendly heterogeneous adhesive includes: 40-60 parts of water-based polyurethane dispersion, 20-40 parts of acrylic emulsion, 10-20 parts of polyisocyanate curing agent, 5-10 parts of epoxy curing agent, 0.1-0.5 parts of defoaming agent, and 0.5-2 parts of thickener; the solid content of the two components of water-based isocyanate including the water-based polyurethane dispersion and the polyisocyanate curing agent in the water-based environmentally friendly heterogeneous adhesive is 40-60%, and the compounding ratio with the curing agent is 100:6-15.

4. The carbon-based lightweight energy-saving material for technological wood veneer according to claim 1 is characterized in that: The preparation method specifically comprises the following steps: S1 carbon-based core material preparation: S11 Ingredient weighing: accurately weigh 25-60 parts of bamboo charcoal powder, 5-15 parts of bamboo activated carbon powder, 10-20 parts of bamboo powder, 40-70 parts of thermoplastic polymer masterbatch, and 1-10 parts of processing auxiliary materials, and pre-bake and heat each material component for 1-2 hours; S12 high-speed stirring: put the weighed bamboo charcoal powder, bamboo powder, thermoplastic polymer masterbatch and processing auxiliary materials into a high-speed mixer, and stir continuously at 1200-1500r / min for 5-10 minutes to ensure that the materials are evenly mixed; S13 melt granulation: the uniformly stirred mixture is transferred to a twin-screw extruder, melt-blended therein, and granulated after extrusion, with the particle size controlled at 10-20 meshes; S14: Mixing and molding again: first, the obtained particles are stirred in a high-speed mixer for 30-60 seconds, then the bamboo activated carbon powder after high-temperature carbonization is added, and stirring is continued for 1-2 minutes, and then the mixture is put into a twin-screw extruder for melt blending and extrusion, and a plate-shaped extrusion mold is used, and water cooling is performed after extrusion; S15 post-processing: Cut the cooled and shaped plates into the standard size required for production, inspect the plates with multiple indicators, and obtain qualified carbon-based core materials for standby use; S2 technology wood veneer processing and compounding: S21 veneer preparation: dry the technical veneer to a moisture content of 8%-12%, pre-bake at 60-80℃ for 2-4 hours, and cut into the same size as the carbon-based core material; S22 adhesive preparation: according to the proportion, take 40-60 parts of waterborne polyurethane dispersion, 20-40 parts of acrylic emulsion, 10-20 parts of polyisocyanate curing agent, 5-10 parts of epoxy curing agent, 0.1-0.5 parts of defoaming agent, and 0.5-2 parts of thickener to prepare waterborne environmentally friendly heterogeneous adhesive, stir at room temperature at 800-1000r / min for 20-30 minutes, and vacuum degassing at -0.08 to -0.1MPa for 10-15 minutes; S23 Uniform Gluing: Use roller coating or spraying to evenly apply glue to the surface, and the amount of glue applied is controlled at 70-130g / ㎡; S24 pre-pressing of the assembly: After the adhesive surface and the carbon-based core material surface are accurately fitted, they are quickly sent into the pre-pressing machine and lightly pressed at a pressure of 0.4-0.6MPa for 5-10 minutes; S25 cold pressing and curing: The carbon-based core material and the high-tech wood veneer composite with the glue-coated surface precisely fitted are then transferred to the cold press, where they are compacted using a three-stage cold press with a pressure of 1.0-2.0MPa and a time of 1.0-3.5h according to the set parameters. The ambient temperature is controlled at 15-25℃ and the humidity at 40-60% throughout the process to obtain the composite carbon-based lightweight energy-saving material with high-tech wood veneer.

5. The carbon-based lightweight energy-saving material for technological wood veneer according to claim 1 is characterized in that: The specific operation of melt granulation in step S13 of the preparation method includes: inputting the uniformly stirred mixture into a twin-screw extruder, setting the screw speed to 200-300r / min for sufficient melt blending, controlling the barrel temperature at 160-190°C, setting the temperature zones according to the material characteristics, the feed section at 160-170°C, the compression section at 175-185°C, the metering section at 180-190°C, the die pressure at 12-18MPa, the obtained particle size is controlled at 10-20 mesh, screened and graded through a vibrating screen, and non-compliant particles are returned for reprocessing.

6. The carbon-based lightweight energy-saving material for technological wood veneer according to claim 1 is characterized in that: In the preparation method step S14 of mixing and molding again, the stirring blades of the high-speed stirrer are double-layer three-blade, the radius ratio of the upper blade to the lower blade is 1-2:1, and the rotation speed is 1300-1500r / min; the twin-screw extruder is set to a temperature of 170-190°C, a pressure of 6-10MPa, and a time of 5-10 minutes; the water-cooled molding system adopts multi-nozzle spray water cooling, a water pressure of 0.3-0.5MPa, a water temperature of 10-20°C, and a circulating water quenching with a cooling rate of 50-80°C / s.

7. The carbon-based lightweight energy-saving material for technological wood veneer according to claim 1 is characterized in that: The specific operation of preparing the adhesive in step S22 of the preparation method includes: taking 40-60 parts of aqueous polyurethane dispersion, 20-40 parts of acrylic emulsion, 10-20 parts of polyisocyanate curing agent, 5-10 parts of epoxy curing agent, 0.1-0.5 parts of defoaming agent, and 0.5-2 parts of thickener according to the proportion, preheating the aqueous polyurethane dispersion and acrylic emulsion at 40-50° C. for 15-20 minutes, and the polyisocyanate curing agent and epoxy curing agent in a dry nitrogen atmosphere , premix at 25-30℃ for 10-15 minutes; mix the preheated adhesive raw materials, stir at a low speed of 300-400r / min for 30-60 seconds, and then increase to 800-1000r / min and stir for 20-30 minutes; the stirred adhesive is transferred to a vacuum degassing tank and degassed at a vacuum degree of -0.08 to -0.1MPa for 10-15 minutes; the degassed adhesive is filtered through a 150-200 mesh filter to remove impurities and undissipated bubbles.

8. The carbon-based lightweight energy-saving material for technological wood veneer according to claim 1 is characterized in that: The specific operation of pre-pressing the preform in step S24 of the preparation method includes: the pre-pressing machine pressure is stabilized at 0.4-0.6MPa, the pressure increase rate is 0.05-0.1MPa / s, the pre-pressing time is controlled at 5-10 minutes, the pre-pressing machine pressure plate adopts a zoned pressure adjustment design, and the pressure is independently controlled in 3-5 zones according to the material size and structural characteristics, the ambient temperature is controlled at 20-25°C, and the humidity is maintained at 40-50%.

9. The carbon-based lightweight energy-saving material for technological wood veneer according to claim 1 is characterized in that: The cold pressing and curing in step S25 of the preparation method is a three-stage operation, specifically including: 0-0.5h is a rapid compaction stage, the pressure is set to 1.5-2.0MPa, the pressure is rapidly increased at a rate of 0.4-0.6MPa / min, the displacement of the cold press plate is controlled at 0.5-1.0mm / min, and the ambient temperature is maintained at 20-22°C and the humidity is 45-50%; 0.5-2.5h is a stable curing stage, the pressure is stabilized at 1.2-1.5MPa, the temperature is controlled at 22-24°C, and the humidity is constant at 48-52%; 2.5-3.5h is a cooling and pressure relief stage, the pressure is linearly reduced to 0-0.3MPa, the pressure reduction rate is 0.1-0.2MPa / h, and the cooling system is started synchronously to cool to 15-18°C at a rate of 5-8°C / h.

10. A cabinet door panel product made of carbon-based light-weight energy-saving material with a technological wood veneer, characterized in that: The cabinet door panel product is made from the technological wood veneer carbon-based lightweight energy-saving material described in any one of claims 1-9.

Citation Information

Patent Citations

  • Artificial wood finishing container floor and manufacturing process thereof

    CN101284593A

  • Functional faced oriented strand board

    CN105729584A

  • Environment-friendly water-based double-component polyurethane anti-corrosion finishing paint and preparation method thereof

    CN108912995A

  • High-speed compounding and online peeling polyurethane transfer adhesive and preparation method thereof

    CN109825239A

  • Waterborne polyurethane adhesive and preparation method thereof

    CN111471424A

Cited By

  • Wood composite carbon-based environment-friendly odorless plate and preparation method thereof

    CN121492186A